2014
DOI: 10.1155/2014/706157
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical Classification in a Population-Based Sample of Psychotic Major Depression and Bipolar I Disorder with 1 Year of Diagnostic Stability

Abstract: The presence of psychotic features in the course of a depressive disorder is known to increase the risk for bipolarity, but the early identification of such cases remains challenging in clinical practice. In the present study, we evaluated the diagnostic performance of a neuroanatomical pattern classification method in the discrimination between psychotic major depressive disorder (MDD), bipolar I disorder (BD-I), and healthy controls (HC) using a homogenous sample of patients at an early course of their illne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 47 publications
3
28
0
1
Order By: Relevance
“…In this context, a recent metaanalysis showed that patients with schizophrenia can be accurately differentiated from healthy volunteers in 80% of the cases using only neuroimaging-based diagnostic models (17). Moreover, these methods may facilitate the development of neuroimaging tools to distinguish among different psychiatric disorders (18)(19)(20)(21) or to predict clinical outcomes (22)(23)(24). Indeed, multiple proof-of-concept studies have successfully used multivariate statistical methods to guide the diagnosis of depression based on structural MRI (sMRI) data (19; 21; 25-27), resting-state functional MRI (rsfMRI) data (26; 28-34), and task-based functional MRI (fMRI) data (35)(36)(37)(38)(39).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, a recent metaanalysis showed that patients with schizophrenia can be accurately differentiated from healthy volunteers in 80% of the cases using only neuroimaging-based diagnostic models (17). Moreover, these methods may facilitate the development of neuroimaging tools to distinguish among different psychiatric disorders (18)(19)(20)(21) or to predict clinical outcomes (22)(23)(24). Indeed, multiple proof-of-concept studies have successfully used multivariate statistical methods to guide the diagnosis of depression based on structural MRI (sMRI) data (19; 21; 25-27), resting-state functional MRI (rsfMRI) data (26; 28-34), and task-based functional MRI (fMRI) data (35)(36)(37)(38)(39).…”
Section: Introductionmentioning
confidence: 99%
“…According to the DSM-IV criteria, each patient was assigned into BD I (22 subjects) or BD II (22 subjects) subgroups. Details on demographic characteristics, and image acquisition and preprocessing can be found in [16]. T1-weighted images were preprocessed according to a number of steps [16], including 1) AC-PC plane alignment; 2) Skull removal; 3) Tissue segmentation into gray matter (GM), white matter (WM), and cerebrospinal fluid (CSF); and 4) High-dimensional image warping to a standard MNI space, resulting in the mass-preserved tissue density maps.…”
Section: Resultsmentioning
confidence: 99%
“…Classification accuracies of 67 and 80% have been reported for the differentiation between depressive and bipolar patients on the basis of MVPA of fMRI data (Mourao-Miranda et al 2012;Grotegerd et al 2014). One study reported only relatively low accuracies for MVPA of sMRI data (Serpa et al 2014), but a more recent study demonstrated 79% classification accuracy for the differentiation between patients with unipolar and bipolar depression , and another study showed 88% accuracy for the differentiation between bipolar patients and patients with schizophrenia (Schnack et al 2014). One DTI study reported accuracies of 72-88% when MVPA was used to differentiate healthy women from female schizophrenia patients (Ota et al 2012).…”
Section: Neuroimagingmentioning
confidence: 99%